FAM98 Family Proteins Play Distinct Roles in Osteoclastogenesis and Bone Resorption - Lei Wang; Tarun Minocha; Bhaba K. Das; Mikaela D. Kunika; Aarthi Kannan; Ling Gao; Subburaman Mohan; Weirong Xing; Kottayil I. Varughese; Haibo Zhao (Biology)
There are three FAM98 family proteins (FAM98A/B/C) in humans and mice. Their physiological functions remain largely unknown. We have previously reported that Fam98a interacts with Plekhm1 in murine osteoclasts and functions in lysosome trafficking/secretion and bone resorption in osteoclasts in vitro. In this study, we found that all three Fam98 genes were expressed in precursor and mature osteoclasts. While the knockdown of Fam98c by a specific short-hairpin RNA (shRNA) in osteoclast precursors attenuated osteoclastogenesis, depletion of Fam98b by an shRNA specifically disrupted osteoclast lysosome trafficking and bone resorption with phenotypes similar to Fam98a shRNA-knockdown in our previous study. Loss of Fam98a in myeloid osteoclast precursors was dispensable for trabecular and cortical bone mass in mice, as well as osteoclastogenesis/bone resorption in vitro, possibly due to compensation by increased Fam98b expression in Fam98a-null osteoclasts. These findings indicate that the three Fam98 proteins play distinct roles in osteoclastogenesis and osteoclast function and need further investigation in future studies.